Moderate- to vigorous-intensity physical activities for hemophilia A patients during low-dose pharmacokinetic-guided extended half-life factor VIII prophylaxis - Chonlatis Srichumpuang; Arunothai Rakmanotham; Chatphatai Moonla; Darintr Sosothikul (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Low-dose pharmacokinetic (PK)-guided extended half-life (EHL) factor VIII (FVIII) prophylaxis can reduce the bleeding risk in hemophilia A (HA) patients. An increase in physical activities for promoting musculoskeletal health may enhance the benefits of prophylactic therapy. Objectives To determine the clinical impact of moderate- to vigorous-intensity physical activities in HA patients during low-dose PK-guided EHL FVIII prophylaxis. Patients/Methods This prospective study enrolled patients with moderate/severe HA (baseline FVIII levels ≤ 5 IU/dL) who had received low-dose PK-guided EHL FVIII prophylaxis for ≥ 6 months. An individualized exercise protocol was introduced to each participant, targeting a 65% increase in the maximum predicted heart rate for ≥ 150 min/week, while continuing low-dose PK-guided EHL FVIII prophylaxis for 6 months. Before and after implementing the intervention, annualized bleeding rates (ABR), annualized joint bleeding rates (AJBR), Hemophilia Joint Health Scores (HJHS), skeletal muscle mass, hemophilia-specific quality-of-life (QoL) scores and annualized FVIII consumption were compared. Results Of 13 participants (mean age ± standard deviation [SD]: 20.1 ± 6.8 years), ABR, AJBR, and HJHS were significantly reduced (mean differences [MD] ± SD: −5.7 ± 2.6 bleeds/year, −4.2 ± 2.6 joint bleeds/year, and −4.3 ± 3.2 marks, respectively; P < 0.05) after applying the 6-month exercise protocol. Skeletal muscle mass and QoL scores had also improved (P = 0.001), while FVIII usage had decreased (MD ± SD: −129.1 ± 208.7 IU/kg/year; P < 0.05). Conclusions The combination of moderate- to vigorous-intensity physical activities with low-dose PK-guided EHL FVIII prophylaxis improves bleeding prevention, musculoskeletal status and QoL in patients with moderate/severe HA. By minimizing FVIII consumption, this strategy helps optimize hemophilia care in countries with budget constraints. ClinicalTrials.gov NCT05728528.